Pengaruh Beban Kerja, Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Dasa Windu Agung Divisi Quality Control - Amanda Eka Febriana; Trigo Moelyo Adhi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Human resources are an important asset in an organisation because they play a direct role in maintaining production processes and output quality. This study aims to analyse the impact of workload, work environment and discipline on employee performance at PT Dasa Windu Agung's Quality Control Division. Employee performance in this division is crucial to ensure that products meet quality standards and prevent defective products (NG) from reaching customers. However, high production targets often interfere with the optimality of the inspection process, potentially reducing output quality. This research is quantitative in nature, using non-probability sampling with a saturated sample category. There were 51 employees who participated in this study. Data were obtained through questionnaires and analysed using multiple linear regression with SPSS 27 for Windows. The simultaneous test (F-test) results showed that workload, work environment, and work discipline simultaneously had a significant impact on employee performance. This was proven by the F-count value of 159.871, which exceeded the F-table value of 2.80. The results of the partial analysis (t-test) showed that workload had a positive but insignificant effect on employee performance, with a t-value of 1.664. The work environment had a significant positive effect with a t-value of 2.398, while work discipline also had a significant positive effect with a t-value of 15.031. An Adjusted R Square value of 0.905 indicates that the three variables are able to explain 90.5% of the variation in employee performance. These results suggest that companies should focus more on improving work discipline and optimising the work environment in order to improve employee performance, while the current workload is not a determining factor.